Exploring the socio-spatial inequalities of Airbnb in Sofia, Bulgaria - Roelofsen, Maartje (ERDKUNDE, 2018)
The objective of this article is to provide an analysis of the spatialities of Airbnb in Sofia, Bulgaria. Relying on an analysis of both quantitative and qualitative data, this article firstly explores the diffusion and concentration of Airbnb listings in the city’s districts. It questions whether the platform’s self-proclaimed contribution to a more diversified offering of tourism accommodation indeed applies to the context of Sofia. It then identifies which listings are most popular among Airbnb guests, and examines who reaps the benefits and profits from this “sharing” economy and who does not. In doing so, this article aims to provide a more nuanced understanding of the power relations in the production and consumption of Airbnb experiences. Whilst discussing the socio-spatial impacts of Airbnb in Sofia, this article takes into account some of the broader urban transformations that have taken place in the city since the end of the socialist regime in 1989. The findings suggest that the large majority of Airbnb listings tend to concentrate in those districts that are marked by commercialization and gentrification and are home to a privileged higher-income population. These areas generally also already benefit from a high concentration of official tourism accommodation and tourist attractions. As such, the article concludes that, like in other European cities, Airbnb benefits a selective number of hosts and potentially further exacerbates an already problematic private rental market.